Population genomic insights into the establishment of non-native golden oyster mushrooms (Pleurotus citrinopileatus) in the United States - Bruce, Andrea L. (My University, 2018)
The naturalization of non-native golden oyster mushrooms (Pleurotus citrinopileatus) represents the first known case of a cultivated mushroom spreading quickly and widely outside of its native range, exhibiting characteristics of invasiveness in the U.S. The first observations of wild fruitings in American woodlands occurred approximately 6 years ago. User-generated biogeographical databases indicate observation frequency has increased significantly over the last two years, with sightings recorded from 9 states so far. To gain insights into the mechanisms behind this species' introduction and spread, I used population genomic data to test the hypothesis that naturalized golden oyster populations are the result of multiple introductions from cultivation operations. I analyzed genome-wide single-nucleotide polymorphisms (SNPs) from 29 wild mushroom specimens collected in six states, plus 6 commercially cultivated isolates. Clustering patterns revealed by the SNP data are consistent with a larger gene pool of commercial strains from which a limited number of strains differentiated via recombination or mutation. High genetic similarity was found between all wild samples plus two of the commercial isolates examined, presenting possible source strains of wild populations. Genotypic subdivision of the wild samples does not closely correlate with geographic location, suggesting multiple introductions and human-mediated spread.
Keywords: Pleurotus Citrinopileatus; Genomics; Fungi